2.2.93 Problems 9201 to 9300

Table 2.187: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

9201

\[ {}x y^{\prime \prime }+\left (x +1\right ) y^{\prime }+2 y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.303

9202

\[ {}x^{2} \left (x^{2}-2 x +1\right ) y^{\prime \prime }-x \left (x +3\right ) y^{\prime }+\left (4+x \right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.355

9203

\[ {}2 x^{2} \left (x +2\right ) y^{\prime \prime }+5 x^{2} y^{\prime }+\left (x +1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.252

9204

\[ {}x^{2} y^{\prime \prime }+4 y^{\prime } x +\left (x^{2}+2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.191

9205

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.200

9206

\[ {}x^{2} y^{\prime \prime }-y^{\prime } x -\left (x^{2}+\frac {5}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.306

9207

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.188

9208

\[ {}x^{2} y^{\prime \prime }+3 y^{\prime } x +4 x^{4} y = 0 \]

[[_Emden, _Fowler]]

0.328

9209

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

0.262

9210

\[ {}y^{\prime \prime }+2 y^{\prime } x +\left (x^{2}+1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.145

9211

\[ {}x^{2} y^{\prime \prime }+y^{\prime } x +\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.188

9212

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.143

9213

\[ {}y^{\prime \prime } = 0 \]

[[_2nd_order, _quadrature]]

0.144

9214

\[ {}y^{\prime \prime } = \frac {2 y}{x^{2}} \]

[[_Emden, _Fowler], [_2nd_order, _linear, ‘_with_symmetry_[0,F(x)]‘]]

0.186

9215

\[ {}y^{\prime \prime } = \frac {6 y}{x^{2}} \]

[[_Emden, _Fowler]]

0.188

9216

\[ {}y^{\prime \prime } = \left (-\frac {3}{16 x^{2}}-\frac {2}{9 \left (x -1\right )^{2}}+\frac {3}{16 x \left (x -1\right )}\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

1.191

9217

\[ {}y^{\prime \prime } = \frac {20 y}{x^{2}} \]

[[_Emden, _Fowler]]

0.157

9218

\[ {}y^{\prime \prime } = \frac {12 y}{x^{2}} \]

[[_Emden, _Fowler]]

0.160

9219

\[ {}y^{\prime \prime }-\frac {y}{4 x^{2}} = 0 \]

[[_Emden, _Fowler]]

0.270

9220

\[ {}x y^{\prime \prime }-\left (2 x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.188

9221

\[ {}y^{\prime \prime }+\frac {y}{x^{2}} = 0 \]

[[_Emden, _Fowler]]

0.266

9222

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+y^{\prime }+y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.680

9223

\[ {}\left (x^{2}-x \right ) y^{\prime \prime }-y^{\prime } x +y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.216

9224

\[ {}x^{2} \left (-x^{2}+2\right ) y^{\prime \prime }-x \left (4 x^{2}+3\right ) y^{\prime }+\left (-2 x^{2}+2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.592

9225

\[ {}y^{\prime \prime } = \frac {\left (4 x^{6}-8 x^{5}+12 x^{4}+4 x^{3}+7 x^{2}-20 x +4\right ) y}{4 x^{4}} \]

[[_2nd_order, _with_linear_symmetries]]

0.579

9226

\[ {}y^{\prime \prime } = \left (\frac {6}{x^{2}}-1\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

0.332

9227

\[ {}y^{\prime \prime } = \left (\frac {x^{2}}{4}-\frac {11}{2}\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

0.296

9228

\[ {}y^{\prime \prime } = \left (\frac {1}{x}-\frac {3}{16 x^{2}}\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

0.208

9229

\[ {}y^{\prime \prime } = \left (-\frac {3}{16 x^{2}}-\frac {2}{9 \left (x -1\right )^{2}}+\frac {3}{16 x \left (x -1\right )}\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

1.043

9230

\[ {}y^{\prime \prime } = -\frac {\left (5 x^{2}+27\right ) y}{36 \left (x^{2}-1\right )^{2}} \]

[[_2nd_order, _with_linear_symmetries]]

86.195

9231

\[ {}y^{\prime \prime } = -\frac {y}{4 x^{2}} \]

[[_Emden, _Fowler]]

0.190

9232

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

[[_2nd_order, _with_linear_symmetries]]

0.272

9233

\[ {}x^{2} y^{\prime \prime } = 2 y \]

[[_2nd_order, _exact, _linear, _homogeneous]]

0.162

9234

\[ {}y^{\prime \prime }+4 y^{\prime } x +\left (4 x^{2}+2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.125

9235

\[ {}x^{2} y^{\prime \prime }-2 y^{\prime } x +\left (x^{2}+2\right ) y = 0 \]

[[_2nd_order, _with_linear_symmetries]]

0.190

9236

\[ {}\left (x -2\right )^{2} y^{\prime \prime }-\left (x -2\right ) y^{\prime }-3 y = 0 \]

[[_2nd_order, _exact, _linear, _homogeneous]]

0.195

9237

\[ {}y^{\prime }-\frac {1}{\sqrt {\operatorname {a4} \,x^{4}+\operatorname {a3} \,x^{3}+\operatorname {a2} \,x^{2}+\operatorname {a1} x +\operatorname {a0}}} = 0 \]

[_quadrature]

4.077

9238

\[ {}y^{\prime }+a y-c \,{\mathrm e}^{b x} = 0 \]

[[_linear, ‘class A‘]]

0.937

9239

\[ {}y^{\prime }+a y-b \sin \left (c x \right ) = 0 \]

[[_linear, ‘class A‘]]

1.361

9240

\[ {}y^{\prime }+2 y x -x \,{\mathrm e}^{-x^{2}} = 0 \]

[_linear]

2.247

9241

\[ {}y^{\prime }+\cos \left (x \right ) y-{\mathrm e}^{2 x} = 0 \]

[_linear]

2.011

9242

\[ {}y^{\prime }+\cos \left (x \right ) y-\frac {\sin \left (2 x \right )}{2} = 0 \]

[_linear]

2.653

9243

\[ {}y^{\prime }+\cos \left (x \right ) y-{\mathrm e}^{-\sin \left (x \right )} = 0 \]

[_linear]

1.520

9244

\[ {}y^{\prime }+y \tan \left (x \right )-\sin \left (2 x \right ) = 0 \]

[_linear]

1.592

9245

\[ {}y^{\prime }-\left (\sin \left (\ln \left (x \right )\right )+\cos \left (\ln \left (x \right )\right )+a \right ) y = 0 \]

[_separable]

1.460

9246

\[ {}y^{\prime }+f^{\prime }\left (x \right ) y-f \left (x \right ) f^{\prime }\left (x \right ) = 0 \]

[_linear]

0.535

9247

\[ {}y^{\prime }+f \left (x \right ) y-g \left (x \right ) = 0 \]

[_linear]

1.436

9248

\[ {}y^{\prime }+y^{2}-1 = 0 \]

[_quadrature]

0.391

9249

\[ {}y^{\prime }+y^{2}-a x -b = 0 \]

[_Riccati]

1.166

9250

\[ {}y^{\prime }+y^{2}+a \,x^{m} = 0 \]

[[_Riccati, _special]]

1.640

9251

\[ {}y^{\prime }+y^{2}-2 x^{2} y+x^{4}-2 x -1 = 0 \]

[[_1st_order, _with_linear_symmetries], _Riccati]

1.760

9252

\[ {}y^{\prime }+y^{2}+\left (y x -1\right ) f \left (x \right ) = 0 \]

[_Riccati]

1.825

9253

\[ {}y^{\prime }-y^{2}-3 y+4 = 0 \]

[_quadrature]

0.575

9254

\[ {}y^{\prime }-y^{2}-y x -x +1 = 0 \]

[_Riccati]

1.362

9255

\[ {}y^{\prime }-\left (x +y\right )^{2} = 0 \]

[[_homogeneous, ‘class C‘], _Riccati]

1.466

9256

\[ {}y^{\prime }-y^{2}+\left (x^{2}+1\right ) y-2 x = 0 \]

[_Riccati]

1.760

9257

\[ {}y^{\prime }-y^{2}+\sin \left (x \right ) y-\cos \left (x \right ) = 0 \]

[_Riccati]

2.981

9258

\[ {}y^{\prime }-y^{2}-y \sin \left (2 x \right )-\cos \left (2 x \right ) = 0 \]

[_Riccati]

4.731

9259

\[ {}y^{\prime }+a y^{2}-b = 0 \]

[_quadrature]

0.392

9260

\[ {}y^{\prime }+a y^{2}-b \,x^{\nu } = 0 \]

[[_Riccati, _special]]

1.748

9261

\[ {}y^{\prime }+a y^{2}-b \,x^{2 \nu }-c \,x^{\nu -1} = 0 \]

[_Riccati]

168.000

9262

\[ {}y^{\prime }-\left (A y-a \right ) \left (B y-b \right ) = 0 \]

[_quadrature]

0.836

9263

\[ {}y^{\prime }+a y \left (-x +y\right )-1 = 0 \]

[_Riccati]

1.453

9264

\[ {}y^{\prime }+x y^{2}-x^{3} y-2 x = 0 \]

[_Riccati]

1.953

9265

\[ {}y^{\prime }-x y^{2}-3 y x = 0 \]

[_separable]

1.955

9266

\[ {}y^{\prime }+x^{-a -1} y^{2}-x^{a} = 0 \]

[_Riccati]

2.108

9267

\[ {}y^{\prime }-a \,x^{n} \left (1+y^{2}\right ) = 0 \]

[_separable]

1.997

9268

\[ {}y^{\prime }+y^{2} \sin \left (x \right )-\frac {2 \sin \left (x \right )}{\cos \left (x \right )^{2}} = 0 \]

[_Riccati]

5.357

9269

\[ {}y^{\prime }-\frac {y^{2} f^{\prime }\left (x \right )}{g \left (x \right )}+\frac {g^{\prime }\left (x \right )}{f \left (x \right )} = 0 \]

[_Riccati]

1.527

9270

\[ {}y^{\prime }+f \left (x \right ) y^{2}+g \left (x \right ) y = 0 \]

[_Bernoulli]

1.861

9271

\[ {}y^{\prime }+f \left (x \right ) \left (y^{2}+2 a y+b \right ) = 0 \]

[_separable]

2.910

9272

\[ {}y^{\prime }+y^{3}+a x y^{2} = 0 \]

[_Abel]

0.517

9273

\[ {}y^{\prime }-y^{3}-a \,{\mathrm e}^{x} y^{2} = 0 \]

[_Abel]

0.800

9274

\[ {}y^{\prime }-a y^{3}-\frac {b}{x^{{3}/{2}}} = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Abel]

9.931

9275

\[ {}y^{\prime }-\operatorname {a3} y^{3}-\operatorname {a2} y^{2}-\operatorname {a1} y-\operatorname {a0} = 0 \]

[_quadrature]

0.680

9276

\[ {}y^{\prime }+3 a y^{3}+6 a x y^{2} = 0 \]

[_Abel]

0.512

9277

\[ {}y^{\prime }+a x y^{3}+b y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _Abel]

2.229

9278

\[ {}y^{\prime }-x \left (x +2\right ) y^{3}-\left (x +3\right ) y^{2} = 0 \]

[_Abel]

0.776

9279

\[ {}y^{\prime }+\left (4 a^{2} x +3 a \,x^{2}+b \right ) y^{3}+3 x y^{2} = 0 \]

[_Abel]

1.155

9280

\[ {}y^{\prime }+2 a \,x^{3} y^{3}+2 y x = 0 \]

[_Bernoulli]

1.255

9281

\[ {}y^{\prime }+2 \left (a^{2} x^{3}-b^{2} x \right ) y^{3}+3 b y^{2} = 0 \]

[_Abel]

0.822

9282

\[ {}y^{\prime }-x^{a} y^{3}+3 y^{2}-x^{-a} y-x^{-2 a}+a \,x^{-a -1} = 0 \]

[_Abel]

4.313

9283

\[ {}y^{\prime }-a \left (x^{n}-x \right ) y^{3}-y^{2} = 0 \]

[_Abel]

1.242

9284

\[ {}y^{\prime }-\left (a \,x^{n}+b x \right ) y^{3}-c y^{2} = 0 \]

[_Abel]

1.312

9285

\[ {}y^{\prime }+a \phi ^{\prime }\left (x \right ) y^{3}+6 a \phi \left (x \right ) y^{2}+\frac {\left (2 a +1\right ) y \phi ^{\prime \prime }\left (x \right )}{\phi ^{\prime }\left (x \right )}+2 a +2 = 0 \]

[_Abel]

1.376

9286

\[ {}y^{\prime }-f_{3} \left (x \right ) y^{3}-f_{2} \left (x \right ) y^{2}-f_{1} \left (x \right ) y-f_{0} \left (x \right ) = 0 \]

[_Abel]

4.105

9287

\[ {}y^{\prime }-\left (y-f \left (x \right )\right ) \left (y-g \left (x \right )\right ) \left (y-\frac {a f \left (x \right )+b g \left (x \right )}{a +b}\right ) h \left (x \right )-\frac {f^{\prime }\left (x \right ) \left (y-g \left (x \right )\right )}{f \left (x \right )-g \left (x \right )}-\frac {g^{\prime }\left (x \right ) \left (y-f \left (x \right )\right )}{g \left (x \right )-f \left (x \right )} = 0 \]

[_Abel]

4.461

9288

\[ {}y^{\prime }-a y^{n}-b \,x^{\frac {n}{-n +1}} = 0 \]

[[_homogeneous, ‘class G‘], _Chini]

2.172

9289

\[ {}y^{\prime }-f \left (x \right )^{-n +1} g^{\prime }\left (x \right ) y^{n} \left (a g \left (x \right )+b \right )^{-n}-\frac {f^{\prime }\left (x \right ) y}{f \left (x \right )}-f \left (x \right ) g^{\prime }\left (x \right ) = 0 \]

unknown

444.434

9290

\[ {}y^{\prime }-a^{n} f \left (x \right )^{-n +1} g^{\prime }\left (x \right ) y^{n}-\frac {f^{\prime }\left (x \right ) y}{f \left (x \right )}-f \left (x \right ) g^{\prime }\left (x \right ) = 0 \]

[_Chini, [_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

3.245

9291

\[ {}y^{\prime }-f \left (x \right ) y^{n}-g \left (x \right ) y-h \left (x \right ) = 0 \]

[_Chini]

1.866

9292

\[ {}y^{\prime }-f \left (x \right ) y^{a}-g \left (x \right ) y^{b} = 0 \]

[NONE]

1.131

9293

\[ {}y^{\prime }-\sqrt {{| y|}} = 0 \]

[_quadrature]

1.392

9294

\[ {}y^{\prime }-a \sqrt {y}-b x = 0 \]

[[_homogeneous, ‘class G‘], _Chini]

4.000

9295

\[ {}y^{\prime }-a \sqrt {1+y^{2}}-b = 0 \]

[_quadrature]

2.466

9296

\[ {}y^{\prime }-\frac {\sqrt {-1+y^{2}}}{\sqrt {x^{2}-1}} = 0 \]

[_separable]

15.224

9297

\[ {}y^{\prime }-\frac {\sqrt {x^{2}-1}}{\sqrt {-1+y^{2}}} = 0 \]

[_separable]

1.857

9298

\[ {}y^{\prime }-\frac {y-x^{2} \sqrt {x^{2}-y^{2}}}{x y \sqrt {x^{2}-y^{2}}+x} = 0 \]

[NONE]

2.767

9299

\[ {}y^{\prime }-\frac {1+y^{2}}{{| y+\sqrt {1+y}|} \left (x +1\right )^{{3}/{2}}} = 0 \]

[_separable]

50.092

9300

\[ {}y^{\prime }-\sqrt {\frac {a y^{2}+b y+c}{a \,x^{2}+b x +c}} = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

109.625